Influence of frequency of energy supplementation on utilization of early-summer, tallgrass prairie forage - Beaty, J.L.; Cochran, R.C.; Lintzenich, B.A.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fifteen ruminally cannulated beef steers were used in a pasture supplementation experiment to determine the effects of frequency of energy supplementation on intake and digestion of tallgrass prairie forage during early to mid-summer. Steers grazed a common pasture and were assigned to the following treatments: no supplement (control); 4 lb rolled sorghum grain/head/day; 9.3 lb grain/head/3 times weekly. Steers in the two supplemented groups consumed the same amount of sorghum grain/head/week. In general, supplementation was not harmful (P =.17) to forage intake. However, providing supplement 3 times weekly tended (P =.11) to depress forage intake compared with daily supplementation. Although supplementation tended (P =.07) to cause selection of less fiber in the diet, total forage digestion tended (P<.07) to be depressed by supplementation. However, total diet organic matter digestibility was not significantly altered by treatment, probably because of the impact of the highly digestible supplement. Based on trends in intake and grazed forage selection, achieving optimal benefit from supplementation of cattle grazing relatively high-quality forage appears more likely when its provided daily rather than 3 times weekly.
Keywords: Beef; Summer range; Energy supplement; Sorghum grain; Forage intake; Forage digestion